Determining the gaussian distribution width of Curie-Weiss temperatures and relaxation times - Skulski, R. (Condensed Matter Physics, 1999)
Some new possibilities of determining the gaussian distribution of Curie-
Weiss temperatures and relaxation times in relaxors and in ferroelectrics
with a diffused phase transition are presented in this paper. The method
of determining the width of gaussian distribution of Curie-Weiss temperatures with the use of the reciprocal of dielectric permittivity on normalized
plots is applied to solid solution Ba(Ti₁₋xSnx)O₃. The method of estimating
the gauss-logarithmic distribution of relaxation times based on normalized
plots is proposed for relaxors. It is shown that the Vogel-Fulcher behaviour
of real and imaginary parts of the dielectric permittivity in PMN is caused
by gauss-logarithmic distribution of relaxation times and by its temperature
dependence. У цій роботі представлено деякі нові можливості щодо визначення гаусового розподілу температур Кюрі-Вейса і часів релаксації у
релаксорах і сегнетоелектриках з розмитим фазовим переходом.
До твердого розчину Ba(Ti₁₋xSnx)O₃ застосовано метод визначення
ширини гаусового розподілу температур Кюрі-Вейса з використанням графіків оберненої діелектричної проникності. Запропонований
графічний метод оцінки гаус-логарифмічного розподілу часів релаксації для релаксорів. Показано, що фогель-фульчерівська поведінка
дійсної та уявної частин діелектричної проникності PMN є наслідком
гаус-логарифмічного розподілу часів релаксації і його температурної залежності.